1994
DOI: 10.1146/annurev.pa.34.040194.001031
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Aflatoxin Carcinogenesis

Abstract: Much progress has been made in elucidating the biochemical and molecular mechanisms that underlie aflatoxin carcinogenesis. In humans, biotransformation of AFB1 to the putative carcinogenic intermediate. AFB-8,9-exo-epoxide, occurs predominantly by cytochromes P450 1A2 and 3A4, with the relative importance of each dependent upon the relative magnitude of expression of the respective enzymes in liver. Genetic variability in the expression of these and other cytochromes P450 may result in substantial interindivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
235
1
2

Year Published

1996
1996
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 680 publications
(238 citation statements)
references
References 19 publications
0
235
1
2
Order By: Relevance
“…This disrupts the normal process of copying DNA and induces mutations. This explains the occurrence of cancer after exposure (Eaton and Gallagher, 1994). Research also indicated that benzo[a]pyrene diol epoxide specifically targets and destroys the protective gene thereby leading to cancer (Pfeifer et al, 2002;Daniel, 2007).…”
Section: Environmentmentioning
confidence: 99%
“…This disrupts the normal process of copying DNA and induces mutations. This explains the occurrence of cancer after exposure (Eaton and Gallagher, 1994). Research also indicated that benzo[a]pyrene diol epoxide specifically targets and destroys the protective gene thereby leading to cancer (Pfeifer et al, 2002;Daniel, 2007).…”
Section: Environmentmentioning
confidence: 99%
“…When reduced to the ground form, it is used as an ingredient in various spice blends and in the food processing industry. Aflatoxins (AFs) are secondary metabolites which are of great concern because of their detrimental effects on human and animal health, including carcinogenic, mutagenic, teratogenic, and immunosuppressive effects (Eaton & Gallagher, 1994), aflatoxins B1, B2, G1 and G2 are normally found in foods (Wogan et al, 2012). They are produced mainly by three species of Aspergillus: Aspergillus flavus, Aspergillus parasiticus and Aspergillus nomius, and can occur in a wide range of important raw food commodities including spices, cereals, nuts, figs and dried fruits.…”
Section: Introductionmentioning
confidence: 99%
“…Depurination of the alkylated base has been correlated to bladder cancer in laboratory mice (8 -10), teratogenic effects in chicken embryos (11), and liver cancer in humans (12)(13)(14). A direct connection between DNA damage and the incidence of human cancer has been established to originate at mutational hot spots of the p53 gene, a tumor suppressor gene whose altered sequence has been associated with approximately 50% of all human cancers (15,16). Aflatoxin B 1 has been found to be responsible in particular for G 3 T transversions at codon 249 of the p53 tumor suppressor gene in hepatocarcinogenesis (17,18) (Scheme I).…”
mentioning
confidence: 99%